Hamstrings‐to‐quadriceps strength and size ratios of male professional soccer players with muscle imbalance. (27th October 2014) - Denadai, Benedito Sérgio; de Oliveira, Felipe Bruno Dias; Camarda, Sérgio Ricardo de Abreu; Ribeiro, Leandro; Greco, Camila Coelho
Summary: The aim of this study was to determine the correlation between the concentric hamstrings/quadriceps muscle strength (Hcon :Qcon ) and cross‐sectional area ratios (Hcsa :Qcsa ) in professional soccer players with Hcon :Qcon imbalance. Nine male professional soccer players (25·3 ± 4·1 years) performed five maximal concentric contractions of the knee extensors (KE) and flexors (KF) at 60 s −1 to assess Hcon :Qcon . The test was performed using the dominant (preferred kicking), and non‐dominant limb with a 5‐min recovery period was allowed between them. Only players with Hcon :Qcon < 0·60 (range: 0·45–0·59) in both limbs were included in this study. The muscle cross‐sectional area (CSA) of KE and KF was determined by magnetic resonance imaging. The correlations between Hcon :Qcon and Hcsa :Qcsa in the dominant leg ( r = −0·33), non‐dominant leg ( r = 0·19) and in the both legs combined ( r = 0·28) were not statistically significant ( P >0·05). Thus, the Hcon :Qcon seems not to be determined by Hcsa :Qcsa in professional soccer players with Hcon :Qcon imbalance.